From Observation to Active Learning : A Collaborative Learning Approach for Object Oriented Programming Course - M, Manikandakumar; S, Sridevi (Journal of Engineering Education Transformations, 2023)
Collaborative learning using Active Learning Strategies (ALS) and Information Communication Technology (ICT) tools in programming subjects facilitate the students-instructors into effective ways to make everyone engaged in Teaching Learning Process. In such learning, learners required to respond one another’s ideas. Teachers are the key players in collaborative learning process by launching the learning environment, accommodating student requirements and ensuring the classroom activities. In this study, benefits of ALS and ICT tool usages have been analyzed for the Object-Oriented Programming course offered to engineering undergraduates. The impacts are analyzed in terms of teaching methodology, practicing lab, pass percentage, course outcome attainment, internal and terminal test performances and course exit survey. The outcomes indicate that, ALS and ICT approach yields positive result in performance.